Virtual Dialog with Maurice Merleau-Ponty. Examining the Traditional Culture in Terms of Perception - Šmitienė, Giedrė (Tautosakos darbai, 2014)
The article stems from a mute and pre-theoretical conviction that an obscure concept of the flesh of the world, introduced by Maurice Merleau-Ponty, can be clarified by the traditional rural lifeworld. on the other hand, it is supposed that the concept of the flesh of the world can help revealing the life-style of the folk. The examination of the traditional culture in the article concentrates on the field research carried out in the lithuanian village. one woman’s way of life and her manner of speech are explored in depth till the common structures of the lived tradition are disclosed. The woman’s relations with plants, animals and things, examined in terms of contents of her speech, but also and even more so – in terms of its style, allow exposing the certain manner of perception that is called in the article diakinaisthetic. in the diakinaisthetic seeing the seer does not objectify what is seen – rather, the seer and the seen come into mutual, reciprocal contact. The perceiver cannot clearly distinguish herself / himself from the perceived as she / he is weaved into the texture of the flesh of the world through the flow of perception. in the field of perception the propensity to mimetism of the traditional rural culture as well as comparisons and parallelisms that abound in the pertinent speech are explained.